Design, Synthesis and Biological Activity Study of γ-Aminobutyric Acid (GABA) Derivatives Containing Bridged Bicyclic Skeletons as BCAT1 Inhibitors - Wen Luo; Zilu Pan; Xinyuan Zhu; Yan Li; Yong Li; Yudi Zhang; Jiamin Pan; Jian Ding; Hua Xie; Guilong Zhao (Molecules)
Branched-chain amino acid aminotransferases (BCATs), existing as the two isoforms BCAT1 and BCAT2, are responsible for the catabolism of branched-chain amino acids (BCAAs) and are highly upregulated and implicated in a diverse range of cancers. BCAT1 inhibitors represent a potential class of therapeutic agents for cancers; however, none have yet progressed to clinical development. Our earlier research identified WQQ-345 as a novel BCAT1 inhibitor featuring a unique bridged bicyclic skeleton and demonstrating both in vitro and in vivo antitumor activity against tyrosine kinase inhibitor (TKI)-resistant lung cancer with high BCAT1 expression. In the present study, we proceeded to modify the structure of WQQ-345 by two-round structure–activity relationship (SAR) exploration, leading to the discovery of a bicyclo[3.2.1]octene-bearing GABA derivative 7. Compound 7 exhibited a 6-fold enhancement in BCAT1 enzymatic inhibitory activity compared to the parent compound WQQ-345 and could effectively suppress the growth of 67R cells that highly expressed BCAT1 and was resistant to third-generation TKIs. GABA derivatives are an important chemical class of BCAT1 inhibitors, and therefore, the findings in the present study represent great progress both in the discovery of potent BCAT1 inhibitors with new chemical structures and in the treatment of cancer resistance.